IMPLEMENTASI PROGRAM BOGOR KERJA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Muhammad Rifal; M. Husein Maruapey; Faisal Tri Ramdani; Oetje Subagdja (Universitas Djuanda Bogor, 2023)
The aim of this research is to describe the implementation of ‘Bogor Kerja’ Program in Bogor City. There are still many people who do not know about ‘Bogor Kerja’ Program in which the availability of its information is presented on the website www.bogorkerja.kotabogor.go.id. The theory used in this research is the theory of Van Meter and Van Horn (1975). The method of this research is a qualitative method with data collection techniques through observation and interviews and then processed so that it can be presented as a research discussion. Data analysis techniques are carried out using data analysis techniques which include data reduction, data display, and conclusions or verification (conclusion drawing). The results of this research conclude that the implementation of ‘Bogor Kerja’ Program facilitates the community in providing the job vacancies, reduces the unemployment rates in Bogor City, and provides the wider employment opportunities, particularly for people of Bogor City.